Reverse Phase HPLC Method for the Analysis of Terbinafine in Pharmaceutical Dosage Forms - N.V. GOPAL, PASUMARTHY; HEMAKUMAR, A.V.; PADMA, S.V.N. (Asian Journal of Chemistry, 2010)
A rapid and sensitive high performance liquid chromatographic method was developed for the estimation of terbinafine in pharmaceutical dosage forms. Terbinafine was chromatographed on a reverse phase C18 column in a mobile phase containing buffer:acetonitrile in the ratio 65:35 v/v. The mobile phase was pumped at a flow rate of 1.8 mL/min and the eluents were monitored at 220 nm. The calibration curve was linear in the range of 20-1000 ng/mL. The intra- and inter-day variation was found to be less than 2 % showing high precision of the assay method. The mean recovery of the drug from the solution containing 20 ng/mL was 99.1 ± 0.73 % indicating high accuracy of the proposed HPLC method may be used for determining terbinafine in bulk drug samples or in pharmaceutical dosage forms.